Higher dietary vitamin C intake is associated with a lower risk of gestational diabetes mellitus: A longitudinal cohort study. Issue 1 (January 2020) - Liu, Chaoqun; Zhong, Chunrong; Chen, Renjuan; Zhou, Xuezhen; Wu, Jiangyue; Han, Juan; Li, Xiating; Zhang, Yu; Gao, Qin; Xiao, Mei; Hu, Xingwen; Xiong, Guoping; et al.
Summary: Background & aims: Oxidative stress has been implicated in the pathogenesis of gestational diabetes mellitus (GDM). Vitamin C as natural antioxidant may help to increase the body's antioxidant capacity. The study is aimed to determine whether vitamin C intake during pregnancy is associated with lower risk of GDM. Methods: Women with singleton pregnancy and without any history of diabetes were drawn from the ongoing Tongji Maternal and Child Health Cohort (TMCHC). Oral glucose tolerance tests (OGTT) were conducted during weeks 24–28 of gestation to screen for GDM. A validated food frequency questionnaire (FFQ) was used to assess dietary intake during mid pregnancy. Use of multivitamins and specific supplements of vitamin C was assessed by questionnaires. Odds ratios (ORs) of GDM risk were calculated by logistic regression models, adjusted for potential confounders. Results: 344 (11.4%) of the 3009 women were diagnosed with GDM. Dietary vitamin C intake was inversely associated with the risk of GDM. Women with above adequate dietary vitamin C intake (more than 200 mg/day) experienced lower odds of GDM (OR 0.68, 95% CI: 0.49–0.95) than those with adequate intake (115–200 mg/day). There was no association between the total consumption of vitamin C and the risk of GDM (OR 1.04, 95% CI: 0.71–1.53). Conclusion: This data suggests that higher dietary consumption of vitamin C during pregnancy is independently associated with lower odds of GDM. Above 200 mg/day of dietary vitamin C intake may help reduce the odds of GDM. However, no such association between total vitamin C intake and the risk of GDM was found. Hence, sufficient vegetables and fruits rich in vitamin C should be recommended to protect pregnant women from developing gestational diabetes.